Ketimpangan Sosial dalam Puisi Jembatan Karya Sutardji Calzoum Bachri: Tinjauan Sosiologi Sastra Alan Swingewood - Kadir, Wahyuni; Mohamad, Inayah Eka Wahyuni; Hidayanti Ali, Ayu (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study analyzes the poem Jembatan by Sutardji Calzoum Bachri using the literary sociology approach developed by Alan Swingewood. The aim of this research is to describe and analyze the social realities of society, the author's social background, and the relationship between literary works and history. This study focuses on three main approaches from Alan Swingewoods theory: literature as a reflection of its time, literature viewed from the production process of authorship, and literature in its relationship with historicity. The research employs a descriptive-analytical method, with data collected by thoroughly reading the poem. The data analysis technique involves identifying, classifying, analyzing, describing, and drawing provisional conclusions about the social realities, the authors background, and the connection between the literary work and historical context.